Peningkatan Penguasaan Materi Taharah Menggunakan Metode STAD pada Peserta Didik SMPN 11 Mataram - Sabekti, Fitri (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2021)
This study aims to determine the increase in the ability to understand taharah material in class VII students of SMP Negeri 11 Mataram by using the STAD type cooperative learning method. This research uses the classroom action research method. The subjects of this study were students of class VII A of SMP N 11 Mataram in the academic year 2019/2020 as many as 30 students consisting of 13 students and 17 students. The results showed that the ability of students to understand the taharah material increased in cycle 1, namely the number of students whose scores were below the KKM or included in the lower group category as many as 10 students or 33.33% and those included in the medium group category as many as 15 students or 50%, while 5 students or 16.67% are in the upper group category, which is getting 85 and above. In cycle 2 the students' abilities increased until there were only two students whose scores were less than the KKM or 6.66%, 17 students or 56.67% got a score range of 78-84, and a total of 11 students or 36.67% were included in the group category. above because it gets a score of 85-100. Increased learning success can also be shown by increasing student activity. Thus, it can be concluded that the STAD method can improve the ability to understand taharah material in class VII students of SMPN 11 Mataram for the 2019/2020 school year.